One Night @ Call Centre: Anxieties and Insecurities of the Rising Indian Working Class: Exploring the Lives and Struggles of Indian Call Center Workers (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Orthodox style of education does not allow the students to think creatively. Even his new ideasare discouraged by his professors. Moreover life will not be tragic if an average student does not get goodgrades. Life is about how one lives it to the fullest without harming the others. His characters know how tolive and take breath in crucial circumstances. Hence one will start pondering upon the purpose of life andthe role of education into it. In One Night the Call Center all the characters live a dolorous life. Theywork at the call center not out of their passion but for some other reasons, mostly financial. In suchdismal condition, the call from God energizes and revitalizes their vision of life. These six people directlyor indirectly represent the ordinary citizens of India. Shyam and Varun in One Night the Call Centeralso suffer economically. Shyam has no father while Varun‗s father does not live with him and hismother. So they have the responsibility to take the charge of their family. They have to continue their jobwithout any interest in it. Radhika has to contribute to run her family smoothly. Being a daughter in law,she has double responsibilities. Esha wants to be model but she has to earn as her parents are againsther ambition. She left them to fulfill her dream while Priyanka‗ mother is such a melodrama queen thatshe becomes successful to convince her daughter for arrange marriage against her will. Her problem isthe pain of every spinster in Indian society. Govind‗s father also lives with other woman and makes himand his mother helpless economically.